Is age just a number or does it really affect the surgical and oncological outcomes after pancreatoduodenectomy? - Saleema Begum; Amjad, Kashmala; Shamoon, Muslim; Jamal, Aun; Syed, Amir Ali; Kabir, Syed Irfan (Journal of the Pakistan Medical Association, 2022)
Objective: To review the impact of age on perioperative and postoperative outcomes in patients following pancreaticoduodenectomy. Method: The retrospective study was conducted at the Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan, and comprised data from January 2014 to December 2018 of all patients who underwent pancreatoduodenectomy. Postoperative morbidity and oncological outcomes were compared between patients aged 60 years in group A and those aged >60 years in group B. Data was analysed using SPSS 20. Results: Of the 161 patients, 103(64%) were males and 58(36%) were females. There were 117(73%) patients in group A; 72(61.5%) males and 45(38.5%) females with an overall mean age of 46±11 years. The remaining 44(27%) were in group B; 31(70.5%) males and 13(29.5%) females with an overall mean age of 67±05 years.The most common pathology was adenocarcinoma 130(81%), commonest site was periampullary 85(53%) and the most common pancreatic reconstruction technique employed was pancreaticogastrostomy 110(68%). Patients in group B had significantly higher comorbidities compared to those in group A (p<0.05). Estimated blood loss during surgery was significantly higher in group B (p=0.004). There was no significant difference in overall morbidity (p=0.856), reoperation (p=1.000), 30-day readmission rate (p=0.097), 90-day mortality rate (p=0.324)) and overall survival (p=0.551) between the groups. Conclusion: Pancreatoduodenectomy could be performed in the elderly with comparable morbidity and oncological outcomes as younger patients. Comorbid conditions remained higher in elderly patients and preoperative optimisation may help improve postoperative outcomes. Key Words: Pancreatoduodenectomy. Outcomes in elderly, Age, Morbidity.